V.I. Vernadskiy: noosphere theory - S. M. Sukhorukova; A. M. Pogoreliy; A. A. Boginskaya (Тонкие химические технологии, 2013)
As the article shows, V.I.Vernadskiy considered noosphere as stage in the process of biosphere`s evolution, which started when a man appeared on Earth. The principle difference between conceptions of "noosphere" and "information field" is described. The history of creating "noosphere theory" as well as conditions for using scientists`s activity for the purpose of safe of biosphere`s unity are also proposed in the article. The importance of economic science in concordance of economic and natural laws for safe of biosphere and further evolution of biosphere into noosphere is noted.